Technology today and tomorrow - Brusic, Sharon (Glencoe/McGraw-Hill, 1999)
Technology: Today and Tomorrow uses a systems-based, problem-solving approach to teaching technology. The text addresses all aspects of technology and includes science and mathematics connections. Fascinating facts, hands-on activities and career choices in technology will keep your students' interest.